Current National Economy and Outlook 2022; Monetary and Financial Sector - Yuliana, Yuliana (Paspama Institute, 2025)
The national economy is experiencing dynamics influenced by domestic and global factors, particularly during the post-COVID-19 pandemic recovery period. This study aims to analyze developments in Indonesia's monetary and financial sector, including implemented policies and challenges faced in 2022. The research method used is descriptive qualitative with a literature review approach, utilizing data from Bank Indonesia, the Ministry of Finance, the Financial Services Authority (OJK), the IMF, and the World Bank. The research findings indicate that more accommodative monetary policy during the pandemic has contributed to economic stability, with interest rate cuts and loosening of liquidity policies. However, various global challenges, such as the Fed's monetary policy normalization, geopolitical tensions between Russia and Ukraine, and global inflation, have also put pressure on the Rupiah exchange rate and domestic financial markets. Meanwhile, the banking sector has demonstrated considerable resilience, with credit growth starting to pick up again, while the capital market and Government Securities (SBN) sectors have faced pressure from capital outflows. Going forward, synergistic monetary and fiscal policies are expected to maintain the momentum of sustainable economic recovery. Financial sector reforms are also needed to strengthen national economic resilience in the face of global uncertainty.